Enhanced efficiencies of sludge dewatering and domestic wastewater treatment by using the bioflocculant from rice stover. (22nd December 2016) - Guo, Junyuan; Du, Jiali; Chen, Peilan; Tan, Xiandong; Huang, Xinyi; Gan, Pengfei; Fu, Lin
Abstract: Potential of a bioflocculant from rice stover was studied in sludge dewatering and domestic wastewater treatment. Production of this bioflocculant showed good correspondence to cell growth, after fermentation for 60 h, the fermentation liquor was obtained, from 1.0 L of which a value of 2.37 g bioflocculant can be extracted, and the main backbone of this bioflocculant was polysaccharides. Without adjusting the sludge's initial pH value of 6.5, when incubated with 18 mg/L of this bioflocculant, dry solids (DS) and specific resistance to filtration (SRF) of the typical wastewater activated sludge reached 18.5% and 4.7 × 10 12 m/kg, respectively, which was better than the ones achieved by Al2 (SO4 )3 and FeCl3 flocculants. For domestic wastewater treatment, after treated by 12 mg/L of this bioflocculant at pH value of 7.5, removal efficiencies of chemical oxygen demand (COD) and turbidity can reach 91.8 and 89.7%, respectively, which were better than the ones achieved by the traditional flocculants such as Al2 (SO4 )3, FeCl3, and polyaluminum chloride (PAC). This study suggested that the bioflocculant from rice stover has great potentials as an alternative flocculant to conventional flocculants in sludge dewatering and domestic wastewater treatment.